Scalable production of nitrogen-doped carbons for multilayer lithium-sulfur battery cells - Kensy, Christian; Haertel, Paul; Maschita, Johannes; Doerfler, Susanne; Schumm, Benjamin; Abendroth, Thomas; Althues, Holger; Lotsch, Bettina; Kaskel, Stefan (Carbon, 2020)
Lithium-sulfur (Li–S) batteries are among the targeted candidates for future generation secondary batteries with high specific energy. Herein, a scalable synthesis is presented to produce highly porous, nitrogen-doped carbons from a commercial carbon black material by melamine impregnation and subsequent thermolysis. The process up-scaling up was demonstrated at > 100 g batch level. The nitrogen doping was controlled through pyrolysis temperatures and carbon to melamine ratio. The sulfur-carbon cathodes exhibit an enhanced cycle life at a moderate electrolyte to sulfur ratio of 7 μL mgS −1. In particular, under lean conditions at low electrolyte amount of 5 μL mgS −1, the nitrogen functionalities improved active material utilization and capacity retention significantly. The nitrogen-doped scaffold was integrated into five-layered prototype cell (71 × 46 mm2) with a capacity of up to 0.87 Ah reaching a specific energy density of 238 Wh kg−1 on stack level. These results provide new insights into realistic application of nitrogen-doped carbons on pouch cell level.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Cathode; Lithium-sulfur battery; Nitrogen-doping; Porous carbon; Pouch cell